2001
DOI: 10.1530/rep.0.1220103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LH on circulating oestradiol and follicular fluid factor concentrations during follicle deviation in cattle

Abstract: Progesterone was used to reduce LH concentrations starting at the time when the largest follicle was > or = 5.7 mm in diameter or well before the expected start of follicle deviation (largest follicle > or = 8.5 mm in diameter). Plasma concentrations of LH, FSH and oestradiol were determined at 4 h intervals in control and progesterone-treated heifers (n = 8 per group). Concentrations of LH were lower (P < 0.05) in the progesterone-treated group, reflecting an absence of the transient increase in LH c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 5 publications
5
15
0
2
Order By: Relevance
“…Hence, the growth of the largest or dominant follicle was not interrupted by the reduced LH until approximately 2 days after the beginning of observed deviation. Similar results have been reported in cattle following a progesterone-induced decrease in LH before deviation [17,18]. Thus, it appears that the LH increase before follicle deviation in both species is not directly involved in initiating diameter deviation but is necessary to support continued growth of the dominant follicle after deviation.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Hence, the growth of the largest or dominant follicle was not interrupted by the reduced LH until approximately 2 days after the beginning of observed deviation. Similar results have been reported in cattle following a progesterone-induced decrease in LH before deviation [17,18]. Thus, it appears that the LH increase before follicle deviation in both species is not directly involved in initiating diameter deviation but is necessary to support continued growth of the dominant follicle after deviation.…”
Section: Introductionsupporting
confidence: 82%
“…As reported in heifers [17,18], experimental reduction of systemic LH concentrations before follicle deviation resulted in reduced intrafollicular concentrations of estradiol and free insulin-like growth factor-1 (IGF-1) but not ir-inhibin of the two largest follicles at the expected beginning of deviation. With regard to the latter, no significant changes in follicular-fluid concentrations of dimeric inhibin-A in the two largest follicles were detected encompassing the expected time of deviation in cows [19].…”
Section: Introductionmentioning
confidence: 73%
“…Several studies demonstrated that LH is involved in follicular selection, and that the incidence of co-dominant follicles is closely associated with an increase in the level of circulating LH during the bovine follicular wave (Ginther et al 1998, Kulick et al 1999, Lopez et al 2004. Suppression of LH secretion by P 4 treatment at the time of follicular deviation decreases follicular E 2 and free IGF1 concentrations and increases IGF-binding protein 2 (IGFBP2) concentration in the follicular fluid of the dominant follicle (Ginther et al 2001b). Pulsatile LH infusion into GNRH agonist-treated cows and during the follicular wave of cyclic cows demonstrated that the LH is required for mRNA expression of steroidogenic enzymes in both granulosa and theca cells, which is responsible for a dramatic increase in the follicular fluid concentration of E 2 and further follicular growth (Crowe et al 2001, Manikkam et al 2001, Hampton et al 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Yuan et al [26] proved mRNA expression of both IGF-I and IGF-II in bovine granulosa cells. Ginther et al [27] reported an increased level of IGF-I in the largest follicles of bovine. However, Armstrong et al [28] were unable to confirm the expression of IGF-I mRNA in bovine granulosa cells, but they found IGF-II expression in the theca cells instead.…”
Section: Changes In Igf Expression During Follicle Atresiamentioning
confidence: 98%